Pressure-Driven Opening and Filling of a Volcanic Hydrofracture Recorded by Tuffisite at Húsafell, Iceland: A Potential Seismic Source - Unwin, Holly E.; Tuffen, Hugh; Phillips, Emrys; Wadsworth, Fabian B.; James, Mike R. (Frontiers in Earth Science, 2021)
Volcanic eruption style can be strongly mediated by the rate and locations of gas escape from magmatic conduits. Gas can escape into the country rock via the propagation and opening of hydraulic fractures and, filled with pyroclastic and lithic particles, these pathways can be recorded as tuffisites. The formation of these features is poorly understood, yet they potentially represent a key role in controlling eruption dynamics. Here we characterise the processes, pressures and timescales involved in tuffisite evolution within country rock, through analysis of the sedimentary facies and structures of a large tuffisite vein, 0.9 m thick and 40 m in length at Húsafell volcano in Deildargil, Húsafell, Iceland. The vein occurs where a propagating rhyolitic sheet intrusion stalled at a depth of ~500 m beneath a strong layer of welded ignimbrite. Laminations, cross-stratification, channels, and internal injections indicate erosion and deposition in multiple fluid pulses, controlled by fluctuations in local fluid pressure and changes in fluid-particle concentration. Assuming each sedimentary unit 0.2 m thick and 40 m in length is the result of a single fluid pulse, we estimate fluid overpressures of 6 MPa were required to emplace each unit, with the tuffisite potentially comprising up to 20 pulses. The relationships between the tuffisite units indicate that the evolving rheology and strength of the compacting fill is important for pressure evolution, together with the system permeability. Characterising tuffisites as the fossil record of fluid-driven hydrofracture opening and evolution can place new constraints on the cycles of pressurisation and outgassing that accompany the opening of magmatic pathways, key to improving interpretations of volcanic unrest and hazard forecasting.